Chemoreactom analysis of cytidyldiphosphocholine indicates synergistic combinations of neuroprotective agents - I. Yu. Torshin; O. A. Gromova; L. A. Mayorova; T. R. Grishina; L. E. Fedotova; A. N. Gromov; I. S. Sardaryan (Неврология, нейропсихиатрия, психосоматика, 2021)
Objective: to establish the molecular mechanisms of interaction of cytidine-diphosphocholine choline (CDP-choline) with other agents used to treat chronic cerebral ischemia (CCI) to increase the effectiveness of the therapy..Material and methods. A chemoreactom analysis of CDP-choline, betahistine, ethyl-methyl-hydroxypyridine succinate  (EMHPS), vinpocetine, and nicergoline was conducted using the  computational methods of the theory of topological analysis of  chemographs.  Results and discussion. The profiles of the pharmacological action of molecules are described, including the accumulation in tissues, pharmacokinetic and pharmacodynamic parameters, the effect on the metabolome and proteome, the survival of neurons during glutamate stress. The mechanisms of the synergistic action of CDP-choline and EMHPS were discovered,  including: 1) inhibition of the activation of the pro-inflammatory  factor NF-κB; 2) decrease in the procoagulant  profile; 3) decrease in glutamate excitotoxicity secondary to  improved oxygen metabolism. These effects result in  conjunction with at least 25 proteins of the human proteome.Conclusion. CDP-choline supports cholinergic  neurotransmission and is used in the treatment of vascular  pathologies of the brain. The cholinergic effect of CDP-choline  is enhanced by the anti-inflammatory, anticoagulant, and  neuroprotective action of both the molecule itself and  synergistic molecules (in particular, EMHPS).